Benjamin Franklin - Sandak, Cass R.; Morris, Richard B. (Franklin Watts New York, 1986)
A biography of the eighteenth-century printer, inventor, and statesman who played an influential role in the early history of the United States.
Includes Bibliography and index
Grade level : 4 - 6
Keywords: Franklin, Benjamin -- 1706-1790; Statesmen -- United States -- Biography -- Juvenile literature; United States -- Constitution